Comparative Genomics Reveals the High Copy Number Variation of a Retro Transposon in Different Magnaporthe Isolates - Singh, Pankaj Kumar; Mahato, Ajay Kumar; Jain, Priyanka; Rathour, Rajeev; Sharma, Vinay; Sharma, Tilak Raj (Frontiers in Microbiology, 2019)
Magnaporthe oryzae is one of the fungal pathogens of rice which results in heavy yield losses worldwide. Extremely variable nature of this fungus has contributed to the evolution of new strains counter key resistance genes in the recently released rice cultivars. Understanding the genomic structure of M. oryzae is essential for appropriate deployment of the blast resistance in rice crop improvement programs. In this study we sequenced two M. oryzae isolates, RML-29 (avirulent) and RP-2421 (highly virulent) and performed comparative study along with three publically available genomes of 70-15, P131 and Y34. We identified several candidate effectors (>600) and isolate specific sequences (>2 Mb) from RML-29 and RP-2421, while a core set of 10013 single copy orthologs were found among the isolates. Repeat analysis revealed ~25 times higher copy number of short interspersed nuclear elements (SINE) in virulent than avirulent isolate. We conclude that the extensive occurrence of SINE throughout the genome could be one of the major mechanisms by which pathogenic variability is emerging in M. oryzae isolates. The knowledge gained in this comparative genome study can provide understandings about the fungal genome variations in different hosts and environmental conditions, and it will provide resources to effectively manage this important disease of rice.